Use of semidefinite programming for solving the LQR problem subject to rectangular descriptor systems - Muhafzan (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the Linear Quadratic Regulator (LQR) problem subject to descriptor systems for which the semidefinite programming approach is used as a solution. We propose a new sufficient condition in terms of primal dual semidefinite programming for the existence of the optimal state-control pair of the problem considered. The results show that semidefinite programming is an elegant method to solve the problem under consideration. Numerical examples are given to illustrate the results.
Keywords: rectangular descriptor system; LQR problem; restricted system equivalent; semidefinite programming